Pemberdayaan Santri Pondok Hutan Agu Pattani Melalui Program Basic English Course: Meningkatkan Akses Global Dan Peluang Pendidikan - Fitriyani Fitriyani; Ahmad Khoiri; Nurma Khusna Khanifa; Kurniawati Mutmainah (Jurnal Informasi Pengabdian Masyarakat, 2024)
English language education is a crucial aspect in preparing individuals to participate in an increasingly interconnected global society. At Pondok Hutan Agu Pattani, Thailand, the Basic English Course program has been introduced with the aim of empowering students by enhancing their English language skills. This study aims to explore the impact of this program on the students' English language development, both academically and personally, as well as to analyze the effectiveness of the teaching methods used in its implementation. This research employs a descriptive analysis of the program's periodic evaluation data and interviews with students and teaching staff to gain in-depth insights into their experiences with the program. The results of the study indicate that the Basic English Course program has significantly improved the students' understanding of basic vocabulary, grammar, and English speaking skills. Interactive teaching methods, such as group activities and role-playing, have proven effective in boosting the students' confidence in using English in real-life situations. Systematic evaluations also show a continuous improvement in their English language abilities over time. In conclusion, the Basic English Course program at Pondok Hutan Agu has not only succeeded in enhancing the students' English proficiency but has also had a positive impact on their personal and professional lives, preparing them to face challenges and opportunities in an increasingly interconnected global society.